The Sharma–Mittal Model’s Implications on FRW Universe in Chern–Simons Gravity - Sarfraz Ali (MDPI AG, 2021)
The Sharma–Mittal holographic dark energy model is investigated in this paper using the Chern–Simons modified gravity theory. We investigate several cosmic parameters, including the deceleration, equation of state, square of sound speed, and energy density. According to the deceleration parameter, the universe is in an decelerating and expanding phase known as de Sitter expansion. The Sharma–Mittal HDE model supports a deceleration to acceleration transition that is compatible with the observational data. The EoS depicts the universe’s dominance era through a number of components, such as <semantics>ω=0</semantics>, <semantics>13</semantics>, 1, which indicate that the universe is influenced by dust, radiation, and stiff fluid, while <semantics>−1<ω<13</semantics>, <semantics>ω=−1</semantics>, and <semantics>ω<−1</semantics> are conditions for quintessence DE, <semantics>Λ</semantics>CDM, and Phantom era dominance. Our findings indicate that the universe is in an accelerated expansion phase, and this is similar to the observational data.